ANÁLISE DA PERCEPÇÃO DOS ACADÊMICOS DE MEDICINA DO PRIMEIRO E QUARTO ANO SOBRE - SÁ, Annah Kehrle de; SANTOS, Mirella Ferreira da Cunha; SARUBBI, Vicente Junior; ANDRADE, Suzany Lisboa Pires de (ANAIS DO ENIC, 2025)
.